Basic science and art of aircraft wreckage reconstruction - Knutson, Donald F. (SAE International, 2020)
Basic Science and Art of Aircraft Wreckage Reconstruction is a unique title which addresses important aspects of investigating crashes, who does this kind of work, and how a healthy attitude and open mind are required to properly perform investigations. It also discusses what to expect from the on-scene part of the investigation, and the fundamental approaches to common types of wreckage reconstruction.
Keywords: Aircraft accidents -- Investigation.; elektronické knihy; electronic books